Vaccination against influenza in patients with rheumatoid arthritis: the effect of rituximab on the humoral response. Issue 7 (2nd November 2007) - Oren, S; Mandelboim, M; Braun-Moscovici, Y; Paran, D; Ablin, J; Litinsky, I; Comaneshter, D; Levartovsky, D; Mendelson, E; Azar, R; Wigler, I; Balbir-Gurman, A; et al.
Abstract : Objective: To assess the effect of rituximab on the efficacy and safety of influenza virus vaccine in patients with rheumatoid arthritis (RA). Methods: The study group comprised patients with RA treated with conventional disease-modifying drugs with or without rituximab. Split-virion inactivated vaccine containing 15 μg haemagglutinin/dose of B/Shanghai/361/02 (SHAN), A/New Caledonian/20/99 (NC) (H1N1) and A/California/7/04 (CAL) (H3N2) was used. Disease activity was assessed by the number of tender and swollen joints, duration of morning stiffness and evaluation of pain on the day of vaccination and 4 weeks later. CD19-positive cell levels were assessed in rituximab-treated patients. Haemagglutination inhibition (HI) antibodies were tested and response was defined as a greater than fourfold rise 4 weeks after vaccination or seroconversion in patients with a non-protective baseline level of antibodies (<1/40). Geometric mean titres (GMT) were calculated in all subjects. Results: The participants were divided into three groups: RA (n = 29, aged 64 (12) years), rituximab-treated RA (n = 14, aged 53 (15) years) and healthy controls (n = 21, aged 58 (15) years). All baseline protective levels of HI antibodies and GMT were similar. Four weeks after vaccination, there was a significant increase in GMT for NC and CAL antigens in all subjects, but not for the SHAN antigen in the rituximab group. In rituximab-treated patients, the percentage of responders was low for all three antigens tested, achieving statistical significance for the CAL antigen. Measures of disease activity remained unchanged. Conclusion: Influenza virus vaccine generated a humoral response in all study patients with RA and controls. Although the response was significantly lower among rituximab-treated patients, treatment with rituximab does not preclude administration of vaccination against influenza.